Dampak Penggunaan QRIS Pada Pelaku UMKM di Kota Padangsidimpuan (Studi Kasus pada Coffee Shop Kopi Koe) - Afifa, Yola; Yarham, M (Jurnal Keuangan dan Perbankan Syariah, 2023)
Technological advances and digitalization have experienced very rapid developments in all social activities, such as in the payment system. This research is field research with a qualitative approach with descriptive research type. Data collection techniques use observation and documentation techniques, direct interviews with micro, small and medium enterprises at the Koe Padangsidimpuan Café Shop. Data analysis techniques include data reduction, data presentation and drawing conclusions. The data validity checking technique uses triangulation to check the validity of the data. The use of QRIS is beneficial for the general public and the café because QRIS can simplify the transaction process in the payment system, but it is very unfortunate because the use of QRIS has no impact on the café's income. The impact of implementing QRIS use is still less than optimal among millennials, This can be seen from the achievement of its user target, which only has a small number of users. Keywords: Use, Quick Response Code Indonesian Standard (QRIS), UMKM.